Impact of Quality of Working Life on Job Engagement “Analytical study of the views of a sample of teaching staff at the University of Kirkuk” - Ahmed Mahmood khalaf (International Journal on Economics, Finance and Sustainable Development, 2022)
This study is concerned with the impact of the quality of working life, the dimensions of which consist of (Working Conditions, Participation in Decision Making, Incentives and rewards, Job Characteristics) In the Promotion of Job engagement among Workers at the University of Kirkuk, the analytical descriptive curriculum has been adopted, the data has been collected by designing a survey identification and distributed to the teaching staff at the University of Kirkuk, and the data has been analyzed according to the certified statistical analysis program One of the most important findings of the study: the research sample answers were found to be close to agreeing with the work quality paragraphs, So by measuring the standard deviation there was no harmony in the answers, This result reflects the fact that the research sample is not interested in quality in working life. The study recommended several recommendations, the most important of which is the need for research organizations to pay attention to the study's changes, especially the quality of life of their employees, as they do not give importance to these important changes.